When history begins to be taught: an analysis of shifting historical representations in Indonesian primary school textbooks - Nanang Suryana; Didin Saripudin; Abdul Razaq Ahmad (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
History education in Indonesian primary schools has been reconfigured following the transition from the 2013 Curriculum to the Merdeka Curriculum, particularly through the shift from Social Studies (IPS) to Natural and Social Sciences (IPAS) as the main subject area in which historical content is introduced. This study examines changes in historical representation across official primary school textbooks under the two curricula. Using a qualitative descriptive design with content analysis, the study analyzes government-issued textbooks published by the Ministry of Education, Culture, Research, and Technology, covering Grade 4–6 IPS textbooks in the 2013 Curriculum and Grade 3–6 IPAS textbooks in the Merdeka Curriculum. The units of analysis include historical narratives, visual representations, and learning activities presented within themes and chapters that contain historical content. To enhance credibility, the analysis was conducted systematically through cross-checking between textbook content, curriculum documents, and relevant policy texts. The findings show that the 2013 Curriculum textbooks primarily emphasize national narratives, heroic figures, and political history, with learning activities tending to focus on reading comprehension and factual recall. In contrast, the Merdeka Curriculum textbooks introduce history earlier through family history, local traditions, community experiences, and context-based inquiry, while Grade 6 expands the discussion to colonialism, independence, and nationalism through a more reflective approach. These findings indicate that curriculum reform has reshaped not only the structure of school subjects but also the pedagogical orientation of history education in primary schools, shifting it from transmissive, national-narrative-based instruction toward a more contextual, inquiry-oriented, and reflective model. This shift has important implications for the development of inclusive history textbooks and for strengthening teachers' capacity to connect local, national, and civic historical learning from an early age.